ASSESSMENT OF HEALTH INFORMATION SEEKING, ACQUISITION AND ADULTS’ PARTICIPATION IN MALARIA CONTROL TOWARDS ACHIEVING MALARIA FREE ZONE IN OGUN STATE (Unilorin Journal of Lifelong Education, 2023)
Malaria remains a life threatening disease responsible for over 600,000 death each year among children, pregnant women and adults with low immunity being mostly affected. The relationship between community prevalence of malaria and health information seeking ability of adults in eliminating the disease is poorly defined. This study therefore investigated the effects of health information seeking and acquisition ability of adults on participation in malaria control in Ogun State, Nigeria. The study employed Health Belief Model using descriptive survey research design of ex-post facto type. Multi-stage sampling technique was used to collect data from 1800 valid questionnaire while those with incomplete responses were discarded. At the first stage, Ogun State was stratified into three strata in line with its Senatorial district Ogun West, Ogun East and Ogun Central. Two local government areas (LGAs) were selected from each stratum with the aid of purposive sampling making a total of 6 LGAs. Simple random sampling technique was finally adopted to select a sample of one thousand, nine hundred and fifty male and female adults from the population ( Odeda-350, Abeokuta South-500,Yewa South-400,Imeko Afon-250, Remo North-150 and Odogbolu300).Instruments used for data collection were Health Information Seeking Ability (r=0.72) Participation in Malaria Control (0.86);Secondary data were also collected from the publications of World Health Organization and National Malaria Elimination Programme. Quantitative data were analyzed using descriptive statistics and chi-square ( ) analysis. The result showed that health information seeking ability had significant contribution to malaria control (=2073.3; df=5,p<0.05).The frequency of malaria control information acquisition was found to be low as majority (46.2%) received malaria control information once in a week. The study therefore recommends among many others high frequency malaria control information dissemination on radio and television and other social media to enhance effective adults’ participation in malaria elimination towards achieving malaria free zone in Nigeria. Conclusively, health education messages should be clear, realistic and reflect local language and behaviour to take care of low literacy level among adults.